Achieving competitive advantage through the use of geographic information systems. (25th June 2007) - Smith, Alan D.
Geographic Information Systems (GIS) are systems that can provide a competitive advantage for firms if used properly in today's market and properly regulated by governmental agencies in cases of security and privacy and planning activities. In this paper, an introduction to the advantages and disadvantages that affect companies who are using a GIS are discussed as well as the organisational benefits/costs that a company may incur by using a GIS, the business strategies/decisions that are enhanced by the use of a GIS, and current companies and governmental agencies (such as the US Justice Department) who have successfully implemented and are currently using GIS. Governmental agencies can increase operational efficiency by enhanced digital data processing, image cleanup, image-enabling (which provides a very powerful tool to visualise imagery and data), and entimeter-level GPS (which allows users to switch from GIS to survey functionality).